PENEGAKAN HUKUM TINDAK PIDANA PROSTITUSI ONLINE DITINJAU DARI UU NO 11 TAHUN 2008 TENTANG ITE - Astrid Frilanda Souisa (Journal of Innovation Research and Knowledge, 2024)
It is evident that law plays an important role in enforcing the rules and regulations within a state. The enforcement of law against online prostitution crimes has not yet been effective or efficient. This situation gives an impression that the enforcement is far from expectations, and this affects the overall process of law enforcement. Law enforcement is heavily influenced by various factors, which hinder the handling of online prostitution crimes. The issue raised in this writing is how law enforcement works against online prostitution crimes in Indonesia and what factors influence the enforcement of law in these cases. This writing shows that law enforcement against online prostitution crimes has not been carried out effectively. This is seen from the fact that there are reports from the public about various places being used for online prostitution. The punishment imposed based on various legal provisions has not been effective. The law enforcement process is influenced by several factors, namely legal factors (laws), law enforcement officers, facilities and infrastructure, society, and culture. These five factors are obstacles to law enforcement, thus hindering the process of enforcing the law in Indonesia. Therefore, law enforcement must be carried out well by law enforcement officers, and extradition agreements should be made to capture perpetrators who are abroad. Efforts should also be made to block websites that are considered harmful to society, especially for children who have been using smartphones from an early age. Thus, online prostitution can be addressed with serious efforts from the government